The magnetic hysteresis characteristics of the meteorites Allende, Canyon Diablo, El Hammami, Ghubara, Gold Basin, Nantan and Sichote Alin - FUNAKI, Minoru; KAPIŠINSKÝ, Igor; TÚNYI, Igor; ORLICKÝ, Oto (Contributions to Geophysics and Geodesy, 2021)
The magnetic hysteresis characteristics of the respective samples have allowed to class as the Carbonaceous Chondrite the Allende meteorite, as the ordinary chondrites the El Hammami, Ghubara and Gold Basin meteorites. But the meteorites Canyon Diablo, Nantan and Sichote Alin have been preferentially classed as the ataxites – Ni-rich iron meteorites, containing mainly taenite, instead of the originally classed as the iron meteorite-coarse octahedrite, IIICD type of iron meteorite and the iron-coarsest octahedrite IIB, respectively.